2019
DOI: 10.48550/arxiv.1909.10842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral isoperimetric inequalities for Robin Laplacians on 2-manifolds and unbounded cones

Abstract: We consider the problem of geometric optimization of the lowest eigenvalue for the Laplacian on a compact, simply-connected two-dimensional manifold with boundary subject to an attractive Robin boundary condition. We prove that in the sub-class of manifolds with the Gauss curvature bounded from above by a constant K• ≥ 0 and under the constraint of fixed perimeter, the geodesic disk of constant curvature K• maximizes the lowest Robin eigenvalue. In the same geometric setting, it is proved that the spectral iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the course of the analysis we employ the co-area formula to prove that under transplantation the kinetic energy R 2 |∇u| 2 dx and the L 2 -norm of the function do not increase, and we use the total curvature identity to show that the potential energy R 2 |u| 2 dµ is preserved. This strategy of the proof is simple but powerful; it was recently successfully applied to the Robin Laplacian on bounded domains [AFK17, BFNT18, FK15], on 2manifolds [KL19], and on exterior domains [KL18,KL20], and also to the two-dimensional Schrödinger operator with δ ′ -interaction supported on a closed curve [L18].…”
Section: Resultsmentioning
confidence: 99%
“…In the course of the analysis we employ the co-area formula to prove that under transplantation the kinetic energy R 2 |∇u| 2 dx and the L 2 -norm of the function do not increase, and we use the total curvature identity to show that the potential energy R 2 |u| 2 dµ is preserved. This strategy of the proof is simple but powerful; it was recently successfully applied to the Robin Laplacian on bounded domains [AFK17, BFNT18, FK15], on 2manifolds [KL19], and on exterior domains [KL18,KL20], and also to the two-dimensional Schrödinger operator with δ ′ -interaction supported on a closed curve [L18].…”
Section: Resultsmentioning
confidence: 99%
“…By the estimate (6) in Lemma 3 we can control the term that contains ∂ s ψ. Namely, for s ∈ (0, a) one has ρ(s, ε) ∈ (0, a), and then one can find some K > 0 such that for any s ∈ (0, a) there holds…”
Section: Upper Bound For the Eigenvalues Of T εmentioning
confidence: 99%
“…For n = 2, the accumulation of eigenvalues at −1 was studied in greater detail in [1]: for δ → 0 + the number N δ of discrete eigenvalues in (−∞, −1 − δ) behaves as N δ ∼ 1 4δ cos 2 θ sin θ . Furthermore, in [6] it was shown that Q ε maximizes the first eigenvalue among all cones with the same perimeter of the spherical cross-section.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral optimization for the lowest Robin eigenvalue in other geometric settings is considered in e.g. [26,30,31]. Isoperimetric inequalities for higher Robin eigenvalues are obtained in [17,18,21].…”
Section: Introductionmentioning
confidence: 99%